Reform and Practice of Hybrid Teaching Mode in Econometrics Course Based on OBE+SPOC - Wu Yan (SHS Web of Conferences, 2023)
This paper presents a study of the hybrid teaching mode for the Econometrics course based on Outcomes Based Education (OBE) and Small Private Online Courses (SPOC). Firstly, the paper by analyzed the issues present in Econometrics teaching. It focuses on the problem of limited course hours and incomplete understanding by beginners in the teaching process of Econometrics; Students lack a solid foundation in mathematics and statistics; Students will operate the software, but the results of the econometric model will not be explained; Insufficient autonomy of students in learning; The lack of up-to-date cases and data has been analyzed. Secondly, the paper proposes a hybrid teaching mode based on OBE+SPOC. Different from traditional MOOC, SPOC is not a "loose management of free range", but a hybrid teaching mode based on OBE+SPOC, which is formed on the MOOC platform and revolves around key links such as "course objectives, course content, classroom implementation, and course evaluation". Thirdly, the practice of the hybrid teaching mode of Econometrics course based on OBE+SPOC is presented.The hybrid teaching mode of Econometrics based on OBE+SPOC provides an effective way to solve the problems in traditional Econometrics teaching. Through the combination of online and offline learning, students can obtain a more flexible and personalized learning experience. Finally, the study concludes with insights into the effectiveness of this model.